2016
DOI: 10.5665/sleep.6314
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Quantity and Quality during Acute Concussion: A Pilot Study

Abstract: Study Objectives: A number of subjective and objective studies provide compelling evidence of chronic post-concussion changes in sleep, yet very little is known about the acute effects of concussion on sleep quality and quantity. Therefore, the purpose of this prospective pilot study was to use actigraphy to examine the changes in sleep quality and quantity acutely following concussion at home rather than in a hospital or sleep laboratory. Methods: Seventeen young adults (7 with acute concussion, 10 controls) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 77 publications
(157 reference statements)
0
44
0
2
Order By: Relevance
“…Depression, anxiety, feelings of isolation, sex, age, learning disorders, family history, and history of migraine headaches are some factors that can contribute to the perpetuation of concussion symptoms . Evidence suggests that sleep disturbances before and immediately following the concussion may contribute to the perpetuation of concussion symptoms …”
Section: Introductionmentioning
confidence: 99%
“…Depression, anxiety, feelings of isolation, sex, age, learning disorders, family history, and history of migraine headaches are some factors that can contribute to the perpetuation of concussion symptoms . Evidence suggests that sleep disturbances before and immediately following the concussion may contribute to the perpetuation of concussion symptoms …”
Section: Introductionmentioning
confidence: 99%
“…A recent prospective study (n = 17) used actigraphy to demonstrate that an increased sleep need might be seen in the acute period following (Raikes and Schaefer 2016). A larger prospective study (n = 748) showed that these changes persist up to one month, but may resolve by one year following TBI; however, increased sleep need was assessed via survey rather than actigraphy (Watson et al 2007).…”
Section: Hypersomniamentioning
confidence: 99%
“…Increased sleep need is a significant issue in the acute period following TBI (Baumann et al 2007;Sommerauer et al 2013;Raikes and Schaefer 2016). A prospective study of 96 patients with TBI demonstrated that 22% experienced hypersomnia following TBI, defined as a sleep need of equal to or greater than 2 h when compared to pre-TBI sleep need (Baumann et al 2007).…”
Section: Hypersomniamentioning
confidence: 99%
See 2 more Smart Citations